Adaptation of software with the nursing process for innovation units - Camila Santana Domingos; Gabriela Tavares Boscarol; Cristiane Chaves de Souza; Meire Chucre Tannure; Tânia Couto Machado Chianca; Patrícia de Oliveira Salgado (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To adapt data collection of the Information System software with the nursing process in Intensive Therapy for use in medical and surgical clinic units. Methods: A descriptive study developed in three stages. The first consisted of team training; in the second, the software was applied in clinical practice with 100 patients; and in the third, we analyzed the modifications to be done. Results: There was inter-observer agreement of 91%, followed by application of the software in 100 patients. In the "patient registration" module, it was suggested the exclusion of one item, inclusion of six and modification of four of them. In the anamnesis screens, no items were flagged to be deleted; 26 inclusions and 7 changes were proposed. In the physical examination screens, it was suggested the exclusion of 31 items, inclusion of 26 and modification of 27. Conclusion: Modifying information systems and going through stages methodologically constructed and implemented was important.